If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + 3) + 8 = -10 Reorder the terms: 3(3 + c) + 8 = -10 (3 * 3 + c * 3) + 8 = -10 (9 + 3c) + 8 = -10 Reorder the terms: 9 + 8 + 3c = -10 Combine like terms: 9 + 8 = 17 17 + 3c = -10 Solving 17 + 3c = -10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 3c = -10 + -17 Combine like terms: 17 + -17 = 0 0 + 3c = -10 + -17 3c = -10 + -17 Combine like terms: -10 + -17 = -27 3c = -27 Divide each side by '3'. c = -9 Simplifying c = -9
| 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a | | 7x-3x+9=29 | | -6x+17=8x+5 | | 5x-19=-7 | | 109-x=167 | | 3+5z= | | 6n-2=-68 | | -2.4k=42 | | b+5-6=18 | | 95+x=x | | 2x=-21+3 | | -0.54=.36m | | 195/200 | | 5+90=x | | 3x-30/18 | | -4-9=13-5x | | 24=4v | | -2/3(8x-9) | | -6(2s+6)= | | 20logx=-50 | | 6x+3-6x= | | (3x-10)=x | | -3y^2-3x=0 | | 30+x+60=180 | | 2x-86=7x+59 | | -3.2/5 | | X+60=x |